O desencantamento do conceito na Dialética Negativa de Theodor Adorno - Mariana Fidelis Jeronimo de Oliveira (2014)
This dissertation analyses the notion of concept in Theodor W. Adornos Negative Dialectics (1966). To do so, we began from the Dialectics of Enlightenment (1947), in which the concept is put in question inside the aporia of reasons critical possibility. Proceeding from this point, we can realize how Negative Dialectics develops this problem as demanding the immanent critique of the concept, what Adorno names disenchantment of the concept. This process is caused, on the one hand, by the critique of the concept forged under the law of identity in Idealisms context and, on the other, by the necessity of the permanence of concept in the context of False State, as a way of critical continuity of reason. From the conscience of non- identity, the disenchantment of the concept is developed as an analysis of the concepts constitution from the scope of the relation subjectobject, shaped according to a primacy of the object. The concept is disenchanted insofar as it is constituted inside a spiritual experience toward the object, and understood as mediation of immediacy. In this way, Adorno expands the notion of concept: it becomes a conceptual activity, capable of breaking the spell of his unitary figure, while putting in relation to intuition and in a reciprocal way, as constellations. Thus, there would be possible a rational and historical understanding of the object, but outside of the impulse to dominate, contributing to the knowledges utopia of approaching the object in its non-identity.